1998
DOI: 10.1046/j.1523-1747.1998.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR for Tyrosinase-mRNA-Positive Cells in Peripheral Blood: Evaluation Strategy and Correlation with Known Prognostic Markers in 123 Melanoma Patients

Abstract: Reverse transcriptase polymerase chain reaction for the detection of tyrosinase-mRNA-positive cells in peripheral blood of melanoma patients, as a possible marker of hematogenous dissemination, has demonstrated varying detection rates. This study examined the sensitivity and reproducibility of the technique using a protocol of multiple polymerase chain reaction to determine circulating melanocytic cells. For each of the 123 melanoma patients included in this study, four nested polymerase chain reactions were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
51
2
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 24 publications
8
51
2
3
Order By: Relevance
“…There is no agreement in the literature as to the percentage of positive tyrosinase determinations in stage III patients, with a wide range of values up to 60%, according to the different studies (Brossart et al, 1993;Kunter et al, 1996;Pittman et al, 1996;Glaser et al, 1997;Farthman et al, 1998;Proebstle et al, 2000;Reinhold et al, 2001). Our results showed a positive tyrosinase expression in 49% of patients.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…There is no agreement in the literature as to the percentage of positive tyrosinase determinations in stage III patients, with a wide range of values up to 60%, according to the different studies (Brossart et al, 1993;Kunter et al, 1996;Pittman et al, 1996;Glaser et al, 1997;Farthman et al, 1998;Proebstle et al, 2000;Reinhold et al, 2001). Our results showed a positive tyrosinase expression in 49% of patients.…”
Section: Discussioncontrasting
confidence: 72%
“…Several studies (Curry et al, 1998;Farthman et al, 1998;Ghossein et al, 1998;Alao et al, 1999;Reinhold et al, 2001) have suggested a potential clinical use of the RT -PCR analysis of tyrosinase mRNA to detect circulating neoplastic cells in the peripheral blood of melanoma patients. In a previous paper , we demonstrated that the majority of untreated stage IV melanoma patients were positive, whereas chemotherapy administration was able to reduce tyrosinase rate, suggesting that tyrosinase may provide a measure of therapy response and be a predictor of disease evolution.…”
mentioning
confidence: 99%
“…Although clinical parameters such as lymph node involvement and thickness of the tumour are helpful, other diagnostic tools are urgently needed to allow for optimal prediction of the clinical course and choice of treatment. For this purpose efforts have been made to detect micrometastases in blood (Brossart et al, 1995;Foss et al, 1995;Hoon et al, 1995;Buzaid and Balch 1996;Mellado et al, 1996;Gläser et al, 1997;Jung et al, 1997;Reinhold et al, 1997;Farthmann et al, 1998;Ghossein et al, 1998;Curry et al, 1998;De Vries et al, 1999;Palmieri et al, 1999) and in the regional lymph nodes by immunohistochemistry or reverse transcriptase polymerase chain reaction (RT-PCR) (Battyani et al, 1993;Wang et al, 1994;Rankin, 1996;Van der Velde-Zimmermann et al, 1996;Blaheta et al, 1998;Goydos et al, 1998;Hatta et al, 1998;Bieligk et al, 1999).…”
mentioning
confidence: 99%
“…Among these techniques the nested RT-PCR is the most sensitive method: in spike experiments the detection limit ranges from 1 to 10 tumour cells in 10 7 peripheral blood lymphocytes (PBLs) (Hoon et al, 1995;Gläser et al, 1997;Jung et al, 1997;Farthmann et al, 1998;Palmieri et al, 1999), whereas for immunohistochemistry the detection limit is 1 tumour cell in 10 5 normal cells (Hatta et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation